2007
DOI: 10.1007/s10620-006-9564-8
|View full text |Cite
|
Sign up to set email alerts
|

Diabetic Rats Supplemented with L-Glutamine: A Study of Immunoreactive Myosin-V Myenteric Neurons and the Proximal Colonic Mucosa

Abstract: We studied the neuronal density and size of myenteric neurons and the epithelial cell proliferation and crypt depth of the proximal colon in diabetic Wistar rats after supplementing them with L-glutamine (1%). The animals were divided into five groups: untreated normoglycemic (UN), L-glutamine-treated normoglycemic (NG), untreated diabetic (UD), and L-glutamine-treated diabetics 4 days (DG4) and 45 days (DG45) days after the onset of diabetes. We observed a reduction of 52.7% and 50.44% in the neuronal density… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
21
0
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 47 publications
5
21
0
1
Order By: Relevance
“…Thus, we can infer that diabetes promoted a reduction of neuron metabolism, leading to the death of a portion of its neuronal population. We observed a reduction of more than half of these neurons, and diabetic neuropathy was observed, similar to studies that used other experimental models of diabetes and evaluated different regions of the gastrointestinal tract, including the stomach (Takahashi et al 1997;Fregonesi et al 2001), duodenum (Pereira et al 2006;Zanoni et al 2011;Lopes et al 2012), jejunum (Defani et al 2003;De Freitas et al 2008;Alves et al 2010;HermesUliana et al 2014), ileum Shotton and Lincoln 2006;Pereira et al 2011), cecum (Zanoni et al 1997;Zanoni et al 2011), and proximal colon (Tashima et al 2007;Roldi et al 2009). The development of neuropathy affects different types of enteric neurons, which are responsible for the control of important functions, such as motility, secretion, blood flow, and growth aspects of the local mucosal immune system (Furness 2012).…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Thus, we can infer that diabetes promoted a reduction of neuron metabolism, leading to the death of a portion of its neuronal population. We observed a reduction of more than half of these neurons, and diabetic neuropathy was observed, similar to studies that used other experimental models of diabetes and evaluated different regions of the gastrointestinal tract, including the stomach (Takahashi et al 1997;Fregonesi et al 2001), duodenum (Pereira et al 2006;Zanoni et al 2011;Lopes et al 2012), jejunum (Defani et al 2003;De Freitas et al 2008;Alves et al 2010;HermesUliana et al 2014), ileum Shotton and Lincoln 2006;Pereira et al 2011), cecum (Zanoni et al 1997;Zanoni et al 2011), and proximal colon (Tashima et al 2007;Roldi et al 2009). The development of neuropathy affects different types of enteric neurons, which are responsible for the control of important functions, such as motility, secretion, blood flow, and growth aspects of the local mucosal immune system (Furness 2012).…”
Section: Discussionsupporting
confidence: 84%
“…Among the chronic complications caused by diabetes, neurological manifestations are the most common, affecting both the autonomic and peripheral nervous systems and impairing the quality of life of patients (Chandrasekharan et al 2011). Our research group found that diabetes mellitus reduced the density of myenteric neurons and enteric neural plasticity in various segments of the digestive system (Takahashi et al 1997;Zanoni et al 1997;Fregonesi et al 2001;Defani et al 2003;Zanoni et al 2003;Pereira et al 2006;Tashima et al 2007;Zanoni et al 2007;De Freitas et al 2008;Roldi et al 2009;Alves et al 2010;Pereira et al 2011;Zanoni et al 2011;Lopes et al 2012;Hermes-Uliana et al 2014). These changes in enteric innervation that arise from diabetes are attributable to persistent hyperglycemia that produces numerous metabolic changes.…”
Section: Introductionmentioning
confidence: 78%
“…Similar results were found by Freitas et al (12) , who observed a significant 37.9% reduction in neuronal density in the jejunum in diabetic animals compared with non-diabetic animals. Other studies performed by our group have analyzed different segments of the gastrointestinal tract, including the ileum (3,22,46) , proximal colon (15,24,25,34,39) , and stomach (14) and showed similar results. This reduction in the number of myenteric neurons results from hyperglycemia, which initiates several biochemical events, such as disturbances in the polyol pathway, formation of AGEs, activation of the protein kinase C and hexosamine pathways, and glycolysis.…”
Section: Discussionsupporting
confidence: 64%
“…Several authors have shown that autonomic neuropathy caused chronically by diabetes mellitus is related to quantitative and morphometric changes in the enteric neurons in various GI segments [22,77,155,156] . However, studies on the number and area of glial cells in diabetes mellitus are scarce.…”
Section: Enteric Gliamentioning
confidence: 99%